Penerapan Pencahayaan Interior pada Hotel Puri Manganti Sesko TNI Bandung - Kindsky, Gio Alfadilah; Zael, Bambang Arief Ruby Rubama (DIVAGATRA - Jurnal Penelitian Mahasiswa Desain, 2024)
Lighting is a a process or method of providing light in a room or environment with the aim of providing adequate light conditions. Lighting encompasses the selection, placement, and configuration of light sources, such as lamps, in order to create lighting conditions that match functional, aesthetic, and comfort requirements. The study aims to discuss the application of interior lighting in two areas of the Purimanganti hotel area, the lobby and the dining room, with the aim of improving the guest experience and creating a pleasant atmosphere. Interior lighting has a significant impact on the atmosphere and aesthetics of the room. In the context of interior decoration, lighting absorption involves careful design considerations related to the type of light used, light distribution, light color, and shadow management. The findings of this study are expected to provide guidance for interior designers and hotel management on how to optimize remuneration. Thus, the application of well-planned lighting can enhance the positive impression of guests. Keywords: lighting, interior, aesthetic, hotel